Religión y Relaciones Internacionales. Genealogías - Iranzo Dosdad, Ángela (Foro Interno, 2006)
Religion’s sudden re-appearance on the scene of international politics has resulted in a creative challenge for the discipline of International Relations. Although the leading tendencies suggest that religion is once again present in international relations, this article will carry out an exercise of introspection within the discipline based on the idea of religious continuity. As a result, questions arise concerning secularization as the foundational myth of modern international relations. This, in turn, will require a genealogical revision of (secular) categories such as international society and the state.